Speedway [videorecording (DVD)] - Taurog, Norman, 1899-1981; Presley, Elvis, 1935-1977; Sinatra, Nancy; Bixby, Bill, 1934-1993; Gordon, Gale, 1906-1995; Schallert, William, 1922-2016 (Warner Home Video, 2007)
"World 600" stock car driver, Steve Grayson, has nerves of steel and a heart of gold. Internal Revenue collection agent Susan Jacks is hot on Steve's trail. When the two meet, it's pedal-to-the-metal action. Kenny Donford, Steve's manager, mismanages Steve into a $145,000 jam and Steve has to figure out how to get out of trouble.